PERSEPSI PUBLIK TENTANG SISTEM EKONOMI, PERBANKAN, BUNGA DAN PENDIDIKAN EKONOMI SYARIAH DI INDONESIA - Sofyan S Harahap; Tatik Mariayanti (Media Riset Bisnis & Manajemen, 2005)
The objective of the research is to observe the people perception towards the capitalist economic system, syariah banking and syariah economic education.. 318 respondents mostley live in Jabotabek consists college students, academic, private employees, entrepreneurs, military of force, and public employees. This research was using the closed questionnaire technique which was distributed on September 25h to December 2005. This research showed that the people has rationalized the capitalist economic system and its danger, and also has rationalized thet the he oyanan economic system. They also expects the government to start considerate the changes of economic system from the capitalist to syariah system. So far, socialization has enough and less rationalized about the at many peopie are not aware of them have accounts on syariah bank and became customer not because they are Moslem. Most of them, 52.5% are still considering that banking interest perceived appropriate to Islamic law. Therefore, they concluded that the government and the department of national education have contributed only small portion in the Syariah economic development and desires the Syariah economic education to start on the early stage, which is from the elementary school.